Assessment of the visibility capabilities of forest fire lookout towers: The case of gemlik, bursa, turkey - Akay, Abdullah Emin (International Society for Photogrammetry and Remote Sensing, 2021)
In Turkey, there are forest areas that are sensitive to fire in the first degree, especially along the coastline in the Marmara region and the Aegean and Mediterranean regions. As a result of forest fires, which is one of the biggest environmental disasters on forest resources, approximately 10000 hectares of forest area is damaged annually. One of the important elements of combating forest fires is early detection. In order to achieve this goal, the correct positioning of fire lookout towers is of great importance. In this study, it was aimed to evaluate visibility capabilities of forest fire lookout tower in Gemlik Forestry Enterprise Chief (FEC) located in the city of Bursa. Firstly, the visibility analysis was implemented using in ArcGIS 10.4.1 to evaluate the existing fire tower in the FEC, and then considering the potential fire lookout tower in the study area, the visible areas from both existing and new tower were determined. According to the results, while 63.55% of the study area was visible from the existing tower, this ratio increased to 77.39% when the second tower was added. When only the forest areas are evaluated, the existing tower could see 71.73% of the forest areas, while the visible forest areas have increased to 83.36% when the two towers were taken into account. It has been seen that the visibility capacities of existing towers and potential towers can be evaluated effectively by using GIS-based visibility analysis.
Keywords: Bursa; Fire Detection; Fire Lookout Towers; Forest Fires; GIS; Visibility Analysis